Formulation of Natural Handsanitizer From Red Belt (Piper Crocatum) Leaves and Aloe Vera (Aloe Vera) - Hasni Yaturramadhan; Cory Linda Futri (Journal of Public Health and Pharmacy)
Itroduction: The government continues to strive so that the Corona virus no longer takes victims due to the Corona virus, of course as Indonesian people support the government's program well. Wash hands with soap so that the Corona Virus that sticks to our bodies is gone and always provide handsanitizer wherever we go. The purpose of this research is that people can make their own hand sanitizer at home.